2016
DOI: 10.1016/j.brainres.2016.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological properties of lumbosacral primary afferent neurons innervating urothelial and non-urothelial layers of mouse urinary bladder

Abstract: Pelvic nerve (PN) bladder primary afferent neurons were retrogradely labeled by intraparenchymal (IPar) microinjection of fluorescent tracer or intravesical (IVes) infusion of tracer into the bladder lumen. IPar and IVes techniques labeled two distinct populations of PN bladder neurons differentiated on the basis of dorsal root ganglion (DRG) soma labeling, dye distribution within the bladder, and intrinsic electrophysiological properties. IPar (Fast blue)- and IVes (DiI)-labeled neurons accounted for 91.5% (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 46 publications
3
44
2
Order By: Relevance
“…The observed R in from the model is in range of values reported in literature for dissociated bladder small DRG neurons i.e. 175 MΩ-581 MΩ [ 7 , 41 ] and is also close to the value reported for intact bladder DRG neurons (332 MΩ) [ 42 ].…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…The observed R in from the model is in range of values reported in literature for dissociated bladder small DRG neurons i.e. 175 MΩ-581 MΩ [ 7 , 41 ] and is also close to the value reported for intact bladder DRG neurons (332 MΩ) [ 42 ].…”
Section: Methodssupporting
confidence: 85%
“…In bladder small afferents neurons, among the many types K + channels expressed, transient A-type (K A ) channel (slowly-inactivating), delayed-rectifier (KDR) and KCNQ/M channels are the predominant ones [ 7 , 10 , 33 , 42 ]. Presence of Ca 2+ -activated K + (K Ca ) channels: large-conductance K Ca (BK Ca ) and small-conductance K Ca (SK Ca ) in bladder small DRG neurons have suggested by some studies [ 30 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The observed proportion of eYFP+ bladder afferents in Scn10a Cre ;Ai32 mice was slightly higher than previous reports of Na v 1.8 expression in 75% of mouse DRG neurons (Shields et al, 2012 ), and higher than the 70%–74% of bladder afferents in rat that exhibit TTX-resistant, Na v 1.8-mediated sodium currents (Yoshimura et al, 1996 , 2006 ; Masuda et al, 2006 ). It is important to note that in all of these studies and in the present study, retrograde labeling of afferent somata was achieved by microinjection of CTβ into the bladder parenchyma, which labels a distinct anatomical subset of non-urothelial, bladder-innervating primary afferents (Kanda et al, 2016 ; Clodfelder-Miller et al, 2017 ). Whether there are differences in the proportion of peri-urothelial afferents in Trpv1 Cre ;Ai32 vs. Scn10a Cre ;Ai32 mice and whether peri-urothelial afferents provide sensory input that is unique from that of the non-urothelial afferents studied here remains to be determined.…”
Section: Discussionmentioning
confidence: 89%
“…For example, 90% of DRG neurons innervating the bladder are phasic (Kanda et al 2016), and capsaicin-sensitive bladder afferents change their firing pattern from phasic to tonic after spinal transection (Takahashi et al 2013). Similarly, Freisinger et al (2013) showed that a higher percentage of renal afferents are tonic (56%) compared to nonrenal afferents (12%).…”
Section: Functional Relationships Associated With Tonic and Phasic Fimentioning
confidence: 99%
“…Retrograde labeling allows characterization of the neurons that innervate specific organs. In some special cases, where the sensory modality is known a priori, this approach allows the study of a functionally defined population (Benson et al 1999;Silbert et al 2003;Connor et al 2005;Freisinger et al 2013;Kanda et al 2016). In addition, genetically modified animals that express a marker (for example, a fluorescent protein) under the control of a gene of interest are useful tools to study the properties of neurons that express that gene (Dussor et al 2008;Tang et al 2016;Le Pichon and Chesler 2014).…”
Section: Introductionmentioning
confidence: 99%